Meta-analysis Evaluating the Efficacy of Statins to Prevent Alzheimer’s Disease - Arig Mesallati; Maha Elgardawi; Aisha Abdelmalik; Kamilah Othman; Doua Idrise (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and aims. Statins are class of drugs that reduce cholesterol by inhibiting 3-hydroxy-3-methylglutaryl-coenzyme A reductase. We carried out this meta-analysis to investigate the correlation between use of statins and the reduction of risk of Alzheimer’s disease (AD), focusing on lipophilicity and hydrophilicity of statins as importatnt determinants of the efficacy of the drugs. Methods. A systemic search was performed of PubMed, Google Scholar databases from their inception to march 2022. Adults with no history of cognitive dysfunction treated with statins were included from high- quality cohort studies. Results.We included eight cohort studies that reported relative risks with 95% confidence intervals for this correlation. A random effects model was used to calculate the summary risk estimates. Studies eligible for analysis involved 707637 participants. The summary of relative risk of Alzheimer’s disease for the statins user was 0.672 (95% CI = 0.479–0.943; P =0.021). In addition, the secondary anaylses showed that both lipophilic and hydrophilic statins induced reduction in the risk of Alzheimer’s disease. The summary of relative risk of Alzheimer’s disease for both hydrophilic and lipophilic statins user were 0.862 (95% CI= 0.0.75-0.991; p = 0.037),0.836 (95% CI= 0.802- 0.871; P= 0.000) respectively. Conclusions. Findings of the present meta-analysis show that statin use was associated with a reduced risk of Alzheimer’s disease (AD), and both hydrohpilic and lipophilic statins are effective in risk reduction. Cite this article. Mesallati A, Elgardawi M, Abdelmalik A, Othman K, Idrise D. Meta-analysis Evaluating the Efficacy of Statins to Prevent Alzheimer’s Disease. Alq J Med App Sci. 2022;5(2):545-555. https://doi.org/10.5281/zenodo.7366675